Analysis of Probable Risk Factors of Gastric Intestinal Metaplasia in Patients Referred to the Gastroenterology Clinic with Dyspepsia - Mahmoudieh, Leila; Salarieh, Naghmeh; Forootan, Mojgan; Fatemizadeh, Somayeh; Ketabi Moghadam, Pardis (Asian Pacific Journal of Cancer Biology, 2023)
Background: Gastric intestinal metaplasia is known as a precursor of gastric cancer in the cascade of events from chronic gastritis to gastric adenocarcinoma. Given the risk of developing gastric cancer in patients with gastric intestinal metaplasia, periodic screening of these lesions for early detection of malignant transformation seems logical. Risk factors of these lesions are worth to be searched and modified due to prevalence and mortality rate of gastric cancer in Iranian population. Material and methods: In this case-control study, 39 patients with and 39 patients without intestinal metaplasia who were attended to the gastroenterology clinic from 2017 to 2021 for upper gastrointestinal endoscopy due to dyspepsia were enrolled. Probable risk factors of gastric intestinal metaplasia were compared between two mentioned groups. Results: According to the presented study, there was a significant link between Turk race (P-value=0.014), couples (p-value=0.033), smoking (p-value=0.009), cholecystectomy (p-value=0.033), active helicobacter pylori infection (p-value=0.018) and prevalence of gastric intestinal metaplasia. There was also a significant association between consumption of fast food (p-value=0.037) as well as proton-pump-inhibitors (p=value=0.028) and risk of gastric intestinal metaplasia. Blood group A was also statistically related (p-value=0.012) to the gastric intestinal metaplasia. Conclusion: According to the results, the chance of metaplasia in Turk race, married people, blood group A, people with history of smoking, active helicobacter pylori infection and history of cholecystectomy is shown to be more than other people. Detrimental diets including fast food as well as consumption of proton-pump-inhibitors were detected to be related to gastric intestinal metaplasia. To corroborate the results, the small sample size of the presented study should be supplemented by more studies with more participants.